2018
DOI: 10.1016/j.jpor.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance and failure modes of polymer infiltrated ceramic endocrown restorations with variations in margin design and occlusal thickness

Abstract: For the restoration of endodontically treated teeth, adding a short axial wall and shoulder finish line can increase the fracture resistance. However, further investigations, especially the fatigue behavior, are needed to ensure this effect applies with small increases of restoration thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 21 publications
7
91
3
6
Order By: Relevance
“…The values of fracture resistance of Vita Enamic endocrowns are comparable to that reported by Taha et al who concluded that the use of polymer infiltrated ceramic material can provide acceptable values of fracture resistance. Also, the values of fracture resistance of VE endocrowns in the current study are considered to be comparable to other CAD/CAM materials with much higher flexural strength like lithium disilicate.…”
Section: Discussionsupporting
confidence: 85%
“…The values of fracture resistance of Vita Enamic endocrowns are comparable to that reported by Taha et al who concluded that the use of polymer infiltrated ceramic material can provide acceptable values of fracture resistance. Also, the values of fracture resistance of VE endocrowns in the current study are considered to be comparable to other CAD/CAM materials with much higher flexural strength like lithium disilicate.…”
Section: Discussionsupporting
confidence: 85%
“…In comparison with the traditional treatment, all ceramic endocrowns have the advantages of good mechanical properties, high biocompatibility, good esthetics, preservation of the remaining tooth structure, and saving time . The available literature has reported that molars restored with endocrowns had good clinical performance and they showed higher fracture resistance than molars restored with fiber post and conventional crowns . Some studies discussed the effect of different preparation shapes on the success of endocrown restorations like ferrule height or pulp chamber extension .…”
Section: Introductionmentioning
confidence: 99%
“…10,[20][21][22] The available literature has reported that molars restored with endocrowns had good clinical performance [23][24][25][26][27][28] and they showed higher fracture resistance than molars restored with fiber post and conventional crowns. 14,29,30 Some studies discussed the effect of different preparation shapes on the success of endocrown restorations like ferrule height 25,31 or pulp chamber extension. 26,28,32 Other studies discussed the effect of the materials factor: ceramic-based or resinbased.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained values of fracture resistance are most likely not indicative of the long term success of the restoration. Nevertheless, it is the most commonly used test to give an indication of a material and a type of restoration suitability as a viable option for clinical situations [3] .…”
Section: Static Loading To Fracture Can Only Show the Strength Of A Rmentioning
confidence: 99%
“…restoration of endodontically treated teeth; yet, none is considered to be the best for all situations [3]. Endocrown is one of the conservative options used to restore root canal treated teeth.…”
mentioning
confidence: 99%